Experimental and Numerical Analysis of Nonlinear Flexural Behaviour of Lattice-Web Reinforced Foam Core Composite Sandwich Panels - Jiye Chen; Hai Fang; Weiqing Liu; Yujun Qi; Lu Zhu (Advances in Civil Engineering)
This paper conducted experimental and numerical analysis of the nonlinear flexural behaviour of lattice-web reinforced foam core composite sandwich panels. Composite sandwich panels composed of a polyurethane (PU) foam core with glass fibre-reinforced polymer (GFRP) composites as the face sheets and lattice webs were fabricated through the vacuum infusion moulding process (VIMP). The flexural behaviour of these composite sandwich panels were experimentally investigated under both uniformly distributed and concentrated loading scenarios. The results showed that reinforced lattice webs can significantly increase the flexural stiffness and load-carrying capacity of sandwich panels and effectively postpone the onset of interfacial debonding failure between the face sheets and core. The effects of the lattice-web height and spacing on the ductility and load-carrying capacities of the sandwich panels were also analysed. Several numerical simulations on lattice-web reinforced foam core composite sandwich panels under concentrated loadings were also conducted. The effectiveness of the finite element (FE) model was validated by the experimental work. Parametric studies indicated that thicker face sheets and lattice webs can remarkably increase the load-carrying capacity. Moreover, the load-carrying capacity and midspan deflection were hardly affected by the foam density.